Insights on the Role of Social Media Tools for B2B SMEs: Case of UK Firms during and after COVID-19 - Huang, Ziyue (2020)
In 2020, the outbreak of COVID-19 has brought about national closure, production stagnation and other serious consequences. In this case, enterprises must ensure the safety of workers and stakeholders while maintaining their business vitality. At the same time, customer behavior and consumption habits are undergoing great changes. Even if the economy recovers from the pandemic in the future, some of these habits will continue to exist. Therefore, this is an opportunity that cannot be missed. COVID-19 has accelerated the electronic process of enterprises and forces them to re-consider the existing business model. Among many kinds of enterprises, small and medium-sized enterprises (SMEs) are insufficient in terms of capital, human resources, material resources, information and technology, and thus are especially affected by COVID-19. The business-to-business sector is also negatively influenced as the upstream of the product or service supply chain. Due to the dynamic delay, it will take longer for B2B companies to recover demand after entering the “new normal”. Under this circumstance, adopting using social media tools can effectively mitigate the impact of the epidemic on B2B SMEs. Therefore, this paper selects B2B SMEs in the UK as the research object, because they are more vulnerable to the negative impact of COVID-19, and the disruptive development of e-commerce technology here is faster. This paper uses the method of qualitative research, conducting semi-structured in-depth interview, to collect data from five executives and key employees of British B2B SMEs to explore how they adjust needs and preferences for using social media tools during and after COVID-19, and understand their attitude towards these tools. By analyzing the information obtained from interviews, the study found that LinkedIn became the most popular tool for B2B SMEs in the UK after the outbreak because it could show the business status and positive attitude of the company to stakeholders and potential customers during COVID-19. Secondly, the response of B2B SMEs in the UK varied in different industries. Among them, companies in the manufacturing industry had more changes in the use of social media tools, including more types of tools and higher frequency of use. But on the whole, there were also ways of behaving that are obviously different from those of large companies. They intended to have longer event-oriented online meetings. Most B2B SMEs used a mixture of social media tools and traditional communication tools to complete the company's projects. The B2B SMEs in the UK showed their affirmation of the role of social media tools during the epidemic. However, some companies in the information industry were not sure whether they would continue their current usage habits after entering the "new normal". Besides the problem that social media tools can not meet all the work needs in one stop, most of the reasons were attributed to the attitudes of companies. They believed that B2B companies should pay more attention to sales, and thought that the large-scale use of social media tools in the normal period can not significantly improve their business performance. Therefore, the integrated use of social media tools requires the joint efforts of tool upgrading and companies' re-recognition of industry trends. Finally, this paper describes the theoretical contribution of the research, business implication for B2B SMEs and the shortcomings of the research, hoping to help enterprises plan ahead of time, predict economic recovery, and prepare for the “new normal”.